Are Founders More Socially Responsible? —An Empirical Research on Private Listed Companies in China - Xiaofei, Shi; Xiaoyu, Zhou; Lisha, Geng (Frontiers in Psychology, 2021)
Personal factors such as the founder's values and psychological characteristics will influence founder's vision, his perception and interpretation of the decision-making environment, and his strategic choice and decision-making. Based on the theory of entrepreneurial characteristics, combined with the founder's unique psychological characteristics, this paper takes Chinese private listed companies between 2010 and 2018 as a research sample to study the effect of the founder of private enterprises on corporate social responsibility. Furthermore, this study analyzes the impact of different management roles of the founder on corporate social responsibility. We demonstrate that the private enterprises have better social responsibility performance when there are founders; the founders have different management roles, and their corporate social responsibility performance has certain differences, and the higher the management level of the founders, the better the corporate social responsibility performance. This paper studies the issue of corporate social responsibility from the perspective of the characteristics of founders, which expands the current framework of corporate social responsibility research and provides an empirical basis for founders to effectively participate in corporate management in practice.